Plasma prothrombin time and activated partial thromboplastin time as predictors of bleeding manifestations during dengue hemorrhagic fever - I. N. Budastra; B. N. P. Arhana; IB. Mudita (Indonesian Pediatric Society, 2009)
Background Massive bleeding and shock are complications ofdengue hemorrhagic fever (DHF) that are associated withhigh mortality. Impaired hemostasis, especially coagulopathy,contributes to bleeding manifestations in DHF. Parameters suchas activated partial thromboplastin time (APTT) and plasmaprothrombin time (PPT) indicate the impact of coagulationsystem.Objective To determine the relationship between APTT and PPTlevels with bleeding manifestations in DHF patients.Methods A prospective cohort study was applied to subjectsdiagnosed with DHF at the Infection and Tropical DiseasesDivision, Department of Child Health, Medical School, UdayanaUniversity, Sanglah Hospital, Denpasar, Indonesia. Laboratorytests to determine APTT and PPT were carried out on thethird, fourth, and fifth day after the onset of fever. Bleedingmanifestations were examined in patients during their hospitalstay. Univariate and Cox regression analyses were performedto examine relationship between APTT and PPT values withbleeding manifestations in DHF patients.Results Forty-three children were enrolled in this study. Therewas a significant relationship between increases in APTT valuewith bleeding manifestations in DHF patients [RR 2.79 (95%CI1.68 to 4.69), P <0.01]. Cox regression analysis showed that onlyincreased APTT values correlated with bleeding manifestations[RR 2.05 (95%CI 1.92 to 3.90), P = 0.02].Conclusion APTT values may be used as a predictor for bleedingmanifestations in DHF.